Actual issues of diagnosis and treatment of irritable bowel syndrome - D. I. Trukhan; V. V. Goloshubina; D. S. Ivanova (Медицинский совет, 2019)
The problem of irritable bowel syndrome (IBS) remains relevant for practice internist and gastroenterologist, as evidenced by the large number of publications in recent years on this issue, affecting various aspects of the pathogenesis, clinical manifestations, diagnosis and treatment of IBS. The article describes the evolution of diagnostic criteria for IBS as part of an international consensus «Rome criteria». Lack of effect of the treatment of IBS ex juvantibus often not a consequence of an incorrect diagnosis, and due to the presence in the patient’s intestinal disorders microbiocenosis. In this situation, it is expedient to correct the microbial landscape of the intestine with the use of probiotic agents. Efficacy in reducing the symptoms of irritable bowel syndrome has reliably demonstrated specific strains of probiotics, such as Bifidobacterium infantis 35624.